1979
DOI: 10.1017/s0003356100023539
|View full text |Cite
|
Sign up to set email alerts
|

The optimum level of protein in the supplement for dairy cows with access to grass silage

Abstract: Grass silage with a dry-matter content of 19·4% and containing 16·7% crude protein was offered ad libitum to 42 first lactation British Friesian cows during the first 75 days post-calving. In addition the animals received supplementary concentrates containing either 10·3, 13·6, 17·3, 21·1, 25·2 or 30·3% crude protein on a fresh weight basis, with extracted soya bean meal being used as the main protein source. All concentrates were offered at an equal level of 8·0 kg per day. The relationship between milk yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 8 publications
4
11
1
Order By: Relevance
“…Both milk protein concentration and milk protein yield increased with increasing protein concentration in the concentrates, confirming the results of previous studies (Gordon and McMurray, 1979). Furthermore, it appears from the results of the present study that milk protein responses to increasing protein concentration are obtained irrespective of the proportion of concentrates in the diet.…”
Section: Responses To Supplementary Proteinsupporting
confidence: 92%
See 1 more Smart Citation
“…Both milk protein concentration and milk protein yield increased with increasing protein concentration in the concentrates, confirming the results of previous studies (Gordon and McMurray, 1979). Furthermore, it appears from the results of the present study that milk protein responses to increasing protein concentration are obtained irrespective of the proportion of concentrates in the diet.…”
Section: Responses To Supplementary Proteinsupporting
confidence: 92%
“…The linear increases in milk yield with increasing protein concentration in the concentrate in this study are in line with the data of Gordon and McMurray (1979). These workers observed that increases in the protein concentration of the concentrates given with grass silage, over the range 103 to 211 g CP per kg fresh weight, resulted in linear increases in milk yield, although the response declined at levels above 211 g CP per kg fresh weight.…”
Section: Responses To Supplementary Proteinsupporting
confidence: 91%
“…On the contrary, protein concentrations were less variable and differences between production systems were slight. It is well assumed that fat and protein production is highly related to nutrition (Gordon & McMurray, 1979;King et al, 1990;Walker et al, 2001), depending not only on the quantity of forage and supplements but also in the composition of them (Palmquist, 1993); Walker et al, 2004). Consequently, differences in fat and protein production depend not only on the production system, but also along the year and the region.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies at this Institute have shown considerable production responses to high levels of protein in the supplementary concentrate given with grass silage (Gordon and McMurray, 1979;Gordon, 1979) and there is also evidence to suggest that this response may be greater with wilted than with unwilted silages (Gordon, 1980a). The present study therefore aimed to provide additional information on the response to supplementary protein, and especially to examine the possibility of any interaction between this response and the pre-wilting of silage.…”
Section: Introductionmentioning
confidence: 94%